The Economics of Fraudulent Accounting - Kedia, Simi; Philippon, Thomas (Review of Financial Studies, 2009)
We argue that earnings management and fraudulent accounting have important economic consequences. In a model where the costs of earnings management are endogenous, we show that in equilibrium, low-productivity firms hire and invest too much in order to pool with high productivity firms. This behavior distorts the allocation of economic resources in the economy. We test the predictions of the model using firm-level data. We show that during periods of suspicious accounting, firms hire and invest excessively, while managers exercise options. When the misreporting is detected, firms shed labor and capital and productivity improves. Our firm-level results hold both before and after the market crash of 2000. In the aggregate, our model provides a novel explanation for periods of jobless and investment-less growth.